1990
DOI: 10.3109/01485019008986875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manganese and Other Divalent Cations on Progressive Motility of Human Sperm

Abstract: Manganese (Mn2+) stimulated the progressive motility of human washed sperm in a time- and dose-dependent manner. This confirmed previous data indicating a capacity for activating the adenylyl cyclase of sperm homogenates in vitro. A maintained response was best seen with doses 0.2-1.0 mM. After an initial stimulation, higher concentrations of up to 20 mM were associated with a decline in the response to control levels. Magnesium ions (Mg2+) stimulated motility in the same dose range but to less than 50% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Activity had been described in the presence of other divalents, such as Co 2ϩ , Ca 2ϩ , and Mg 2ϩ , but Mn 2ϩ -dependent activity was always significantly higher (19,25,26). We purified the 48-kDa isoform of human sAC fused to GST and confirmed that its K m for ATPMn 2ϩ (ϳ0.8 mM) was indistinguishable from the value obtained for sAC activity purified from rat testis (14) and matched the values reported for soluble cAMP-producing activity in testis and sperm from a variety of mammals (11,21,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activity had been described in the presence of other divalents, such as Co 2ϩ , Ca 2ϩ , and Mg 2ϩ , but Mn 2ϩ -dependent activity was always significantly higher (19,25,26). We purified the 48-kDa isoform of human sAC fused to GST and confirmed that its K m for ATPMn 2ϩ (ϳ0.8 mM) was indistinguishable from the value obtained for sAC activity purified from rat testis (14) and matched the values reported for soluble cAMP-producing activity in testis and sperm from a variety of mammals (11,21,27).…”
Section: Discussionmentioning
confidence: 99%
“…In this report we confirm that calcium directly stimulates sAC activity and that calcium functions independently from calmodulin to increase the affinity of sAC for its substrate ATP-Mg 2ϩ . Regulation by calcium, which is capable of supporting catalytic activity in the absence of Mg 2ϩ (19,25,26), suggests that sAC, like tmACs, utilizes two metals in its active site; however, the active center of sAC would function best with different metals. It is possible that Ca 2ϩ , which lowers the apparent K m for substrate ATP-Mg 2ϩ , would be better at coordinating ATP, while Mg 2ϩ would serve as the catalytic metal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature about the effects of magnesium concentration on sperm parameters refers mostly to other than avian species. In humans, sperm cell motility was enhanced by 0.2−1.0mM of Mg 2+ , while higher concentration led to the same motility compared to control levels (Magnus et al, 1990). In sea urchin, as well as in humans, Mg 2+ has been found to increase viability of spermatozoa in dose-dependent manner (Dawson et al, 1998).…”
mentioning
confidence: 92%
“…It has been found that Mn 2+ supplementation stimulated adenylate cyclase (membrane bound enzyme) activity in sperm, which in turn enhanced the level of cAMP. 25,26 This increase in concentration of cAMP through a cascade of events phosphorylated the axonemal protein, which are involved in sperm motility. Therefore, in the present study, increase in hyperactivity with Mn 2+ (200 mM) supplementation is associated with adenylate cyclase activity.…”
Section: Discussionmentioning
confidence: 99%